2020
DOI: 10.3390/foods9010035
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Transference and Antimicrobial Activity of Cheeses Made with Ewes’ Milk Fortified with Essential Oils

Abstract: During the last decades, essential oils (EOs) have been proven to be a natural alternative to additives or pasteurization for the prevention of microbial spoilage in several food matrices. In this work, we tested the antimicrobial activity of EOs from Melissa officinalis, Ocimum basilicum, and Thymus vulgaris against three different microorganisms: Escherichia coli, Clostridium tyrobutyricum, and Penicillium verrucosum. Pressed ewes’ cheese made from milk fortified with EOs (250 mg/kg) was used as a model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Thus, the large consumption of basil as a food ingredient makes it a possible candidate for biofortification purposes (Kiferle et al, 2019). Currently, several studies have demonstrated the use of basil essential oil in foods as an antioxidant in meat and dairy products, antibacterial in sausages, antifungal in links, and several other applications (Falowo et al, 2019;Gaio et al, 2015;Kocić-Tanackov et al, 2020;Licon et al, 2020).…”
Section: Food and Cosmetic Industrymentioning
confidence: 99%
“…Thus, the large consumption of basil as a food ingredient makes it a possible candidate for biofortification purposes (Kiferle et al, 2019). Currently, several studies have demonstrated the use of basil essential oil in foods as an antioxidant in meat and dairy products, antibacterial in sausages, antifungal in links, and several other applications (Falowo et al, 2019;Gaio et al, 2015;Kocić-Tanackov et al, 2020;Licon et al, 2020).…”
Section: Food and Cosmetic Industrymentioning
confidence: 99%
“…Mohamed et al [51] evaluated the effect of different extracts of Moringa oleifera leaves on the growth of probiotic bacteria in a cream cheese: both ethanolic and aqueous extracts did not inhibit the LAB growth, but ethanolic extract resulted in a higher growth. Licón et al [52], instead, reported that essential oil of Melissa officinalis, at a concentration of 250 mg/kg, was not suitable as antimicrobial in pressed ewes' cheese, because it showed inhibitory effect against lactic acid bacteria starter cultures, unlike essential oils of Ocimum basilicum and Thymus vulgaris.…”
Section: Relevant Aspects Concerning the Use Of Natural Preservatives In Cheese Makingmentioning
confidence: 99%
“…Owing to their antibacterial and antioxidant properties, essential oils can be used as potential natural preservatives in different foods, including flavored drinks (Cava et al, 2007). Flavored milk has increased in popularity in recent years; nevertheless, there are few data available in literature about the effect of adding essential oils directly to milk before cheese-making (Licon et al, 2020).…”
Section: Microbiological and Ph Analysismentioning
confidence: 99%